Penile agenesis in adult. - Momen, MA; Haque, MM; Akhter, S; Ahmed, M; Rabbani, MG; Rahman, N (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Jul;20(3):493-496 The abstract of this article is available on the PubMed website